The relationship between sensory stimuli integration and visual preferences in small urban parks - Shahhoseini, Habib; M.S., Mustafa Kamal; Maulan, Suhardi; Samim, Paniz Mousavi (Iran University of Science and Technology, 2023)
Small Urban Parks (SUP) are vital parts of cities that can enhance the quality of the public environment. Visual Preferences (VP) in SUPs, which consist of diverse stimuli, are affected by multisensory perception, including the combination of auditory, olfactory, and tactile stimuli. However, the relationship between sensory stimuli integration (sound, smell, touch) and people’s VP has been neglected during the design process, which can influence the assessment of an environmental aesthetic and preferences. The main objective of the present study is to evaluate how multisensory can affect the VP of visitors through textual and photo questionnaires. Structural Equations Model and Regression were studied on 394 participants, chosen from 16 SUPs located in different parts of Tabriz, Iran. Results identified the “Human and Natural sounds, Human-Body and Natural smells” as influential factors on visitors’ VP; however, touch stimuli had no significant impact. In this regard, paying attention to the visitors’ experience of Natural Sound-Smell Stimuli and the Human-body Sound-Smell Stimuli are essential in designing SUPs. The outcomes of the current research provide a guideline for city planners and landscape designers regarding the relationship between senses and their practical implications in SUPs in order to promote people’s VP and visitation.